STRESS AND JOB SATISFACTION AMONG POLYTECHNIC LECTURERS IN MALAYSIA: A NEED ANALYSIS STUDY - Mohd Ramlee, Muhammad Firdaus; Abu Bakar, Abu Yazid (Bisma The Journal of Counseling, 2020)
The World Health Organization (WHO) reports that stress is a global epidemic and that the United Nations (UN) is reporting workplace stress labeled as a 'disease' of the 20th century. The more complex and dynamic an organization is, the higher the source of stress. Work stress comes from many aspects such as job management characteristics, organizational relationships, workload, organizational structure and climate, job characteristics and more. Excessive work stress not only adversely affects the organization but also affects the physical and mental health of employees and family relationships. Failure to control work pressure will also affect job satisfaction. As such, This concept paper analyzes the need to conduct stress and job satisfaction studies among polytechnic lecturers in Malaysia. This analysis is not only intended to catalyze this research, but it also has the potential to assist polytechnic management in developing workplace stress management programs and improving job satisfaction among lecturers